Penerapan Model Pendidikan dengan Meneladani Akhlak Rasulullah di Era Disrupsi - Fatimah, Nur (STAI Nurul Islam Mojokerto, 2024)
The revolution in the field of information technology has now been able to fundamentally change the social order of society. The presence of information technology provides a lot of convenience for humans, but also has a destructive side that threatens the younger generation. This study through a literature review aims to analyze the extent of the urgency and strategy of moral education for the young generation of Islam in the era of Disruption. Some of the results of this study indicate the increasing importance of moral education for the younger generation, even becoming a primary need. Some causes of various moral problems that are increasingly rampant with very easy access to information technology. Therefore, several steps are needed to build individuals who have good morality, including 1) providing good examples for young people, 2) providing a comprehensive understanding of the concept of morality, 3) preventing students from getting carried away by pleasure and luxury, 4) strengthening the relationship between educators and students, 5) using various methods according to the conditions of students according to their era, 6) building and controlling the student environment.